THE ROLE OF SOCIAL MEDIA IN PROMOTING DOMESTIC TOURISM: AN APPLIED STUDY OF FACEBOOK USERS IN ALGERIA (International Journal of Innovative Technologies in Economy, 2025)
Social media has experienced widespread growth in recent years and has been extensively leveraged across diverse fields, including tourism promotion. This study aims to elucidate the role of social media, particularly Facebook, in promoting domestic tourism in Algeria. A descriptive–analytical methodology was adopted, with a sample of 150 Facebook users surveyed via an online questionnaire. The results indicate a strong positive correlation between Facebook use and the promotion of domestic tourism. The Pearson correlation coefficient was 0.748, whereas the regression coefficient was B = 0.580, suggesting that increased Facebook use contributes to strengthening domestic tourism promotion. The study further concludes that producing engaging content and enhancing trust in social media posts are key factors in attracting domestic tourists. Accordingly, a set of recommendations is proposed to improve and maximize the use of these platforms.